2010
DOI: 10.1007/s00127-010-0209-z
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of hospitalised schizophrenia in Finland since 1980: decreasing and increasing again

Abstract: Changes in the number of psychiatric beds available, admission policy and diagnostic practice may explain the majority of variations in FARsch. Possibly, increased use of illegal drugs and improved treatment of depression are reflected in the increase in FARsch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
1
16
1
1
Order By: Relevance
“…This approach has been used in several register and birth cohort studies (Isohanni et al 2001;Wahlbeck et al 2001;Bresnahan et al 2005;Bray et al 2006;Thorup et al 2007;Jörgensen et al 2010;Sørensen et al 2010;Salokangas et al 2011;Kodesh et al 2012;Vanasse et al 2012;Sutterland et al 2013). Although nearly all of these studies reported higher IRs for schizophrenia than first-contact studies, their findings have not been included in the core estimates in the meta-analyses, and neither have they been interpreted as evidence that a longitudinal sampling frame results in higher incidence estimates (Anderson, 2013).…”
Section: Introductionmentioning
confidence: 94%
“…This approach has been used in several register and birth cohort studies (Isohanni et al 2001;Wahlbeck et al 2001;Bresnahan et al 2005;Bray et al 2006;Thorup et al 2007;Jörgensen et al 2010;Sørensen et al 2010;Salokangas et al 2011;Kodesh et al 2012;Vanasse et al 2012;Sutterland et al 2013). Although nearly all of these studies reported higher IRs for schizophrenia than first-contact studies, their findings have not been included in the core estimates in the meta-analyses, and neither have they been interpreted as evidence that a longitudinal sampling frame results in higher incidence estimates (Anderson, 2013).…”
Section: Introductionmentioning
confidence: 94%
“…As a result of the mental healthcare actions in Finland, outpatient mental health visits increased (from 1.6 million to 2.3 million) during 1997-2010 period (Pirkola & Sohlman, 2005). The admissions of adolescent patients more than doubled between 1991 and 2003 (Salokangas et al 2011). Earlier psychosis detection due to more options in mental health services could partially explain higher rates of psychosis in the NFBC 1986 than in the NFBC 1966, but also the decrease of the most severe forms of psychosis.…”
Section: Health System Changes and New Registersmentioning
confidence: 99%
“…However, since the prevalence and incidence of schizophrenia have been reported to vary considerably [3][4][5][6][7][8][9] between and within countries and because very few recent studies have provided estimates within Canada or within the province of Quebec, it is vital to gain information on the magnitude of this disease at the population level in order to develop appropriate interventions when required.…”
mentioning
confidence: 99%